Prenatal genetic detection in foetus with gallbladder size anomalies: cohort study and systematic review of the literature - Yimo Zeng; Rong Hu; Jian Lu; Yiming Qi; Dan Chen; Chaoxiang Yang; Jing Wu (Annals of Medicine)
Objectives The aim of the study was to evaluate the detection rate of genetic abnormalities in cases of foetal gallbladder (FGB) size abnormalities to determine whether these abnormalities justify prenatal diagnosis.Methods Two hundred and twenty-seven foetuses with gallbladder (GB) size anomalies who underwent prenatal diagnosis between January 2015 and June 2024 were included in the study. All these patients underwent chromosomal microarray and/or karyotyping, and 37 cases also underwent whole exome sequencing (WES). Two hundred and eight cases were followed up for postnatal outcomes. Then, we reviewed the literature of FGB anomalies cases with confirmed chromosomal results.Results The study included 227 foetuses, comprising 60 cases with isolated GB size anomalies and 167 cases with non-isolated GB size anomalies. Non-isolated GB size anomalies were associated with findings such as hyperechogenic bowel, ventriculomegaly, foetal growth restriction (FGR), cardiac anomalies, renal dysplasia and single umbilical artery. The overall diagnostic yield of genetic tests was 10.57% (24/227). Aneuploidies were identified in seven foetuses. Pathogenic/likely pathogenic copy number variations (CNVs) were found in nine foetuses, and α0-thalassemia in five foetuses. Additionally, three pathogenic single-nucleotide variants (SNVs) were detected through WES. Foetuses with non-isolated GB size anomalies showed a higher rate of detecting genetic abnormalities compared to those with isolated GB size anomalies, with a significant difference in statistical analysis (13.2% vs. 3.3%, p = .033, Chi-square test). A total of eight studies, involving 407 cases met the criteria for inclusion in the systematic review. Overall, 28 foetuses were identified to have chromosomal abnormalities (6.9%, 28/407).Conclusions This study indicates that parents of foetuses with GB size anomalies should be informed about the potential for aneuploidy, pathogenic CNVs and SNVs, and genetic testing should be recommended in cases of non-isolated foetal GB size anomalies.